Exergaming and Aquatic Exercises Affect Lung Function and Weight Loss in Obese Children - Irandoust, Khadijeh; Taheri, Morteza; H’mida, Cyrine; Neto, Gabriel Rodrigues; Trabelsi, Khaled; Ammar, Achraf; Souissi, Nizar; Chtourou, Hamdi; Nikolaidis, Pantelis T.; Rosemann, Thomas; Knechtle, Beat (International Journal of Sports Medicine, 2020)
We investigated the effect of exergames and aquatic exercises on lung function and weight loss in obese children. Sixty-one obese male primary-school children were randomly allocated to video game, aquatic exercise, and control groups. Lung functions and anthropometric variables were measured before and after the intervention and after one month (follow-up). In the video game group, an Xbox Kinect game was played for 60 min during three sessions a week. The aquatic aerobic exercise was performed three times per week and consisted of a warm-up, main exercises, and a cool down phase. For the video game group, there was a significant reduction in body weight between (i) pre- and (ii) post-intervention and follow-up. In the aquatic exercise group, there was a significant reduction in body weight between pre- and post-intervention and between pre-intervention and follow-up. Both exercise groups improved the waist/hip ratio index compared to the control group. Forced vital capacity was significantly improved in the follow-up of the video game group and the aquatic exercise group compared to the control group. A significant improvement was found in forced expiratory volume in the first second at post-intervention and follow-up in the video game and the aquatic exercise groups. Exergames and aquatic exercises improved weight loss and lung function in obese children.
Keywords: games; activity; aquatic; lung function; obese